Molecular Mechanisms Underlying Vibrio Tolerance in Ruditapes philippinarum Revealed by Comparative Transcriptome Profiling - Yin, Zhihui; Nie, Hongtao; Jiang, Kunyin; Yan, Xiwu (Frontiers in Immunology, 2022)
The clam Ruditapes philippinarum is an important species in the marine aquaculture industry in China. However, in recent years, the aquaculture of R. philippinarum has been negatively impacted by various bacterial pathogens. In this study, the transcriptome libraries of R. philippinarum showing different levels of resistance to challenge with Vibrio anguillarum were constructed and RNA-seq was performed using the Illumina sequencing platform. Host immune factors were identified that responded to V. anguillarum infection, including C-type lectin domain, glutathione S-transferase 9, lysozyme, methyltransferase FkbM domain, F-box protein, heat shock 70 kDa protein, Ras-like GTP-binding protein RHO, C1q, and BTB/POZ domain protein. Ten genes were screened and verified by RT-qPCR, and the expression results were consistent with those of RNA-seq. The lectin gene in the phagosome pathway was expressed at a significantly higher level after V. anguillarum infection, which might indicate the role of lectin in the immune response to V. anguillarum. Comparing the results from R. philippinarum resistant and nonresistant to V. anguillarum increases our understanding of the resistant genes and key pathways related to Vibrio challenge in this species. The results obtained here provide a reference for future immunological research focusing on the response of R. philippinarum to V. anguillarum infection.